IDENTIFICATION OF SALMONELLA SPP. IN MOTELO TURTLES (GEOCHELONE DENTICULATA) OF A ZOO FARM IN IQUITOS CITY - Ruiz M., Nelson (2010)
The objective of the present study was to detect the presence of Salmonella spp. in 30 motelo turtles (Geochelone denticulata) in a zoo of the Iquitos region, Peru. Fecal samples were obtained by rectal swaps and processed by bacteriological and biochemical cultivation tests. The results showed that 6.7% of the samples were positive to Salmonella spp. and the typing indicated Salmonella enterica subspecies enterica serotype typhimurium.